PESANTREN AND MODERNITY IN INDONESIA: MA’HAD ALY OF KUNINGAN - Didin Nurul Rosidin (Hunafa: Jurnal Studia Islamika, 2012)
Abstract: In Indonesia where the majority of the population is Muslims, pesantren that has thrived since the arrival of Islam to the shore of the archipelago is still out of the central field of the national educational system. As such, pesantren was and is forced to continually be aware with ongoing new educational developments in the country as the result of modernisation and globalisation. The foundation of Ma’had Aly is one of the ways taken by the pesantrens to response to the current developments within Muslim communities, to define or even maintain their central roles as well as to preserve their tradition in such a modernised and globalised Indonesia. By exploring the foundation of Ma’had Alys in Kuningan as a case study, this article closely elaborates how the pesantren world engages these processes both in their cirricular settings and practices and provides how it negotiates with the ongoing changes within its surrounding communities.Key Word: Pesantren, modernity, Ma’had ‘Ali Kuningan